Pedagogical Exploration of Ethnomathematics: Efforts to Contextualize Numeracy Strategies for Elementary School Children - Firmansyah; Anwar Novianto; Dafid Slamet Setiana; Fitriana Tjiptasari; Gumpanat Boriboon (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2026)
This study aims to integrate ethnomathematics into numeracy instruction in non-formal education settings and to test the effectiveness of its application in improving the numeracy skills of elementary school-aged children through non-formal education, with the goal of creating contextual and meaningful learning experiences. The study was conducted in Sukodono Village, Pacitan, which possesses a wealth of contextual cultural practices that serve as a resource for numeracy learning. The methods used were a mixed-methods study with an ethnographic approach to explore cultural practices, as well as a one-group pretest–posttest pre-experimental design to test improvements in numeracy skills. The research subjects consisted of cultural experts, teachers, elementary school-aged children, and parents, with a sample size of 16 students selected using purposive sampling. Quantitative data were analyzed using a paired samples t-test and N-Gain, while qualitative data were analyzed using the Miles and Huberman model. The research findings indicate that various local cultural practices contain mathematical concepts relevant to numeracy learning, such as geometry, measurement, patterns, and comparisons, which were identified in the contexts of agate stones, the Ceprotan traditional ceremony, and Rontek art. The findings suggest a trend toward improved student numeracy skills, as evidenced by moderate N-Gain scores and significant differences in paired t-test results. These findings confirm that the integration of ethnomathematics into numeracy learning not only strengthens contextual conceptual understanding but also serves as a relevant and meaningful alternative learning strategy, particularly within non-formal education pathways rooted in local culture.